Preclinical development of a miR-132 inhibitor for heart failure treatment - Foinquinos, Ariana; Batkai, Sandor; Genschel, Celina; Viereck, Janika; Rump, Steffen; Gyöngyösi, Mariann; Traxler, Denise; Riesenhuber, Martin; Spannbauer, Andreas; Lukovic, Dominika; Weber, Natalie; Zlabinger, Katrin; et al. (Nature communications, 2020)
Despite proven efficacy of pharmacotherapies targeting primarily global neurohormonal dysregulation, heart failure (HF) is a growing pandemic with increasing burden. Treatments mechanistically focusing at the cardiomyocyte level are lacking. MicroRNAs (miRNA) are transcriptional regulators and essential drivers of disease progression. We previously demonstrated that miR-132 is both necessary and sufficient to drive the pathological cardiomyocytes growth, a hallmark of adverse cardiac remodelling. Therefore, miR-132 may serve as a target for HF therapy. Here we report further mechanistic insight of the mode of action and translational evidence for an optimized, synthetic locked nucleic acid antisense oligonucleotide inhibitor (antimiR-132). We reveal the compound’s therapeutic efficacy in various models, including a clinically highly relevant pig model of HF. We demonstrate favourable pharmacokinetics, safety, tolerability, dose-dependent PK/PD relationships and high clinical potential for the antimiR-132 treatment scheme. miR-132 was shown to drive pathological cardiac remodeling, a hallmark of heart failure. Here, the authors show that an antisense inhibitor of miR-132 has favourable pharmacokinetics, safety-tolerability and preclinical efficacy in mouse and porcine models of heart failure.